“Such as might have arisen only out of hell”: A Note on Poe’s Hellenic Motifs in “The Black Cat” - Tsokanos, Dimitrios; Ibáñez, José R. (Complutense Journal of English Studies, 2018)
Edgar Allan Poe’s “The Black Cat” has received a great deal of scholarly attention over the years from a variety of perspectives, not least the domestic and symbolic presence of Pluto in the story. Kent Ljungquist (1980) saw Poe’s narrative in terms of classical literary tradition, specifically the notion of the daemonic, yet confined his study to Pluto’s demonic features, arguing that the cat may be an infernal spirit sent to castigate the narrator. Other studies, such as Clark Moreland and Karime Rodriguez (2015), have reached similar conclusions. However, there is a surprising absence in the literature of any discussion of Poe’s decision to name the ‘phantasm’ of his narrative after the Hellenic god of the Underworld. The present paper seeks to address this, and proposes that Poe’s Pluto may not simply function as a demonic spirit, but rather as the Pluto of Hellenic mythology himself.